Unraveling the Space of Sasak Women in the Nensek Tradition - Hani Saroya, Liza; Fadjri, Muhammad (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2025)
This research aims to explain the idea of the presence of Sasak women's space in the nensek tradition in Keloke Hamlet. This study uses the Ricoeur hermeneutic approach. Data to explain this was obtained through field observations and interviews. The findings, including those related to women's space and its existence, are explained by the existence of high life values that support the nensek tradition. Among them, it is seen as a religious value that is the basis for the formation of women's space and then becomes a cultural mandate that requires every woman to be a grandmother and be able to be a grandmother. The nensek tradition is seen to continue to grow, in line with the ideals by which Sasak Keloke women can reflect to see themselves in their life journey. In other words, with the nensek tradition inherited from their ancestors and the survival of women's space as a cultural mandate, Sasak women can meet their ancestors again, which is also proof that they have carried out their duties as heirs of the culture left by their ancestors.